Improved rare mercury recovery from fluorescent lamp wastes through simultaneous leaching and heating - Karamzadeh L.; Salahi E.; Mobasherpour I.; Rajabi A.; Javaheri M. (Springer Science and Business Media Deutschland GmbH, 2025)
Mercury is one of the main components of fluorescent lamps. Considering the adverse effects of mercury on human health and the environment, recovery of mercury-containing fluorescent lamps is very important in developed countries. The glass parts of used fluorescent lamps are among the dangerous wastes whose mercury content should be reduced to the lowest possible level according to international standards. The aim of this research is to achieve a systematic approach to minimize the amount of mercury present in fluorescent lamp glass residues according to the European Commission EC95/2002 regulations. In order to extract mercury from glasses, glass pieces were washed with deionized water, using stirring to increase washing efficiency. In order to achieve the maximum amount of extraction, parameters such as ratio of glass to deionized water (S/L), stirring time, temperature and pH were changed. The results showed that, the highest mercury extraction rate is about 98% and in the conditions S/L = 0.1, stirring time of 12h, temperature of 60C and pH 1, which is using a combination of HCl and H3PO4 acid 5% with a ratio of 1:4 has been obtained. The success of this method not only increases environmental sustainability, but also classifies the resulting glass waste as non-hazardous. ? The Author(s), under exclusive licence to Tehran University of Medical Sciences 2024.